Strategic Intervention in Housing Development Case Study: Indonesia - Sugiyantoro, . (Center for Research and Community Services ITB, 2001)
Strategic, intervention has important meaning in urban policy, urban planning and urban management. Central to this concept is collaborative approach for inclusion of all stake holders. This paper exercising strategic intervention approach in the field of housing policy in Indonesia. Using two rnodel (Pugh Model and Kelvani & Werna Model) (his paper proposes model for strategic intervention in housing provision in Indonesia.